2012
DOI: 10.1071/cp12191
|View full text |Cite
|
Sign up to set email alerts
|

Australian Legume Research – synthesis and future directions

Abstract: The Australian Legumes Symposium was the first in a planned series of regular technical symposia organised by the Australian Grasslands Association. The aim was to provide researchers with the opportunity to interact, present up-to-date reviews on topics related to pasture legume science, present results of current research and participate in planning of future research and development relevant to pasture legumes. This paper is intended to be the key output of the forum – a summary of findings and highlights f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…bacteria and forage legumes (Iannetta et al 2016). Additionally, biological N 2 fixation may reduce the environmental impact caused by inorganic N fertilisers while improving nutrient cycling in the ecosystem (Virgona et al 2012;Boddey et al 2020). Kohmann et al (2018) reported greater release of litter N in grasslegume mixtures of bahiagrass (Paspalum notatum Flugge cv.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…bacteria and forage legumes (Iannetta et al 2016). Additionally, biological N 2 fixation may reduce the environmental impact caused by inorganic N fertilisers while improving nutrient cycling in the ecosystem (Virgona et al 2012;Boddey et al 2020). Kohmann et al (2018) reported greater release of litter N in grasslegume mixtures of bahiagrass (Paspalum notatum Flugge cv.…”
Section: Introductionmentioning
confidence: 99%
“…2016). Additionally, biological N 2 fixation may reduce the environmental impact caused by inorganic N fertilisers while improving nutrient cycling in the ecosystem (Virgona et al . 2012; Boddey et al .…”
Section: Introductionmentioning
confidence: 99%
“…Dietary supplementation with forage legumes not only increases livestock production primarily via higher intake, nutrient content, and digestibility than cereal crops such as grasses, sorghum, maize, etc. [8,9], but also improves the rumen with fermentation efficiency via enhanced metabolisable energy, protein ratios and ruminal bypass protein availability to animals [10]; increased N retention [11]; and reduced methane emissions [8,12,13]. Combining annual forage legumes with crops such as maize may present an enhanced feeding option for animals in arid regions [14].…”
Section: Introductionmentioning
confidence: 99%
“…Tree legumes, however, have not been assessed to the same extent as herbaceous legumes. There have been successes in Africa (Wambugu et al, 2011;Franzel et al, 2014), Asia (Hasniati and Shelton, 2005), Australia (Virgona et al, 2012), and South America (Xavier et al, 2014;Hernández-Muciño et al, 2015;Apolinário et al, 2015), but the extent of their adoption in livestock production systems is still limited. There are several tree legume species with potential for utilization in extensively managed warm-climate areas.…”
Section: Introductionmentioning
confidence: 99%